Role of age and sex in short-term and long term mortality after a first Q wave myocardial infarction. Issue 7 (1st July 2001) - Marrugat, J; Gil, M; Masiá, R; Sala, J; Elosua, R; Antó, J M; ,
Abstract : STUDY OBJECTIVE: The objective of this study was to analyse whether the risk of death within 28 days and three years after a first Q wave myocardial infarction was higher in hospitalised women than in men. DESIGN: Follow up study. PATIENTS AND SETTING: All consecutive first Q wave myocardial infarction patients aged 25 to 74 years (447 women and 2322 men) admitted to a tertiary hospital in Gerona, Spain, from 1978 to 1997 were registered and followed up for three years. MAIN RESULTS: Women were older, presented more comorbidity and developed more severe myocardial infarctions than men. A significant interaction was found between sex and age. Women aged 65–74 had higher early mortality risk than men of the same age (OR 1.62; 95% CI 1.01, 2.66) after adjusting for age, comorbidity and acute complications including heart failure. Women under 65 tended to be at lower risk of early mortality than men (0.45 (95% CI 0.19, 1.04). Three year mortality of 28 day survivors did not differ between sexes. CONCLUSIONS: These data support the idea that the higher 28 day mortality in hospitalised women with a first Q wave myocardial infarction is mainly attributable to the large number of patients aged 65 to 74 years in whom the risk is higher than that in men. Women under 65 with myocardial infarction do not seem to be a special group of risk.